Progress and prospects for the control of HIV and tuberculosis in South Africa: a dynamical modelling study - Dr Brian G Williams, PhD; Somya Gupta, MA; Matthew Wollmers, MA; Reuben Granich, MD (Elsevier, 2017)
Background: In September, 2016, South Africa adopted a policy of providing antiretroviral treatment to everyone infected with HIV irrespective of their CD4 cell count. Studies of universal treatment and expanded prevention of HIV differ widely in their projections of effects and the associated costs, so we did this analysis to attempt to find a consensus. Methods: We used data on HIV from the Joint UN Programme on HIV and AIDS (UNAIDS) from 1988 to 2013 and from data from WHO on tuberculosis from 1980 to to 2013 to fit a dynamical model to time trends in HIV prevalence, antiretroviral therapy (ART) coverage, and tuberculosis notification rates in South Africa. We then used the model to estimate current trends and project future patterns in HIV prevalence and incidence, AIDS-related mortality, and tuberculosis notification rates, and we used data from the South African National AIDS Council to assess current and future costs under different combinations of treatment and prevention approaches. We considered two treatment strategies: the Constant Effort strategy, in which people infected with HIV continue to start treatment at the rate in 2016, and the Expanded Treatment and Prevention (ETP) strategy, in which testing rates are increased, treatment is started immediately after HIV is detected, and prevention programmes are expanded. Findings: Our estimates show that HIV incidence among adults aged 15 years or older fell from 2·3% per year in 1996 to 0·65% per year in 2016, AIDS-related mortality decreased from 1·4% per year in 2006 to 0·37% per year in 2016, and both continue to fall at a relative rate of 17% per year. Our model shows that maintenance of Constant Effort will have a substantial effect on HIV but will not end AIDS, whereas ETP could end AIDS by 2030, with incidence of HIV and AIDs-related mortality rates both at less than one event per 1000 adults per year. Under ETP the annual cost of health care and prevention will increase from US$2·3 billion in 2016 to $2·9 billion in 2018, then decrease to $1·7 billion in 2030 and $0·9 billion in 2050. Over the next 35 years, the expansion of treatment will avert an additional 3·8 million new infections, save 1·1 million lives, and save $3·2 billion compared with continuing Constant Effort up to 2050. Expansion of prevention, including provision of pre-exposure prophylaxis, condom distribution, and male circumcision, could avert a further 150 000 new infections, save 5000 lives, and cost an additional $5·7 billion compared with Constant Effort. Interpretation: Our results suggest that South Africa is on track to reduce HIV incidence and AIDS-related mortality substantially by 2030, saving both lives and money. Success will depend on high rates of HIV testing, ART delivery and adherence, good patient monitoring and support, and data to monitor progress. Funding: None.